A Case of Severe Respiratory Failure Caused by Metapneumovirus and Influenza Virus in a Patient with HIV Infection - Luca Pipitò; Chiara Vincenza Mazzola; Eleonora Bono; Claudia Gioè; Giovanni M. Giammanco; Celestino Bonura; Antonio Cascio (Viruses)
Background: Human metapneumovirus (HMPV) is a significant cause of respiratory infections, particularly in children, the elderly, and immunocompromised individuals. However, data on HMPV infection in people living with HIV (PLWH) are limited, and cases of co-infection with influenza A virus in this population have not been previously described. Case Presentation: We reported the case of a 73-year-old HIV-positive man with multiple comorbidities, including insulin-dependent diabetes mellitus, who presented with fever, asthenia, and glycometabolic decompensation. Despite an initially unremarkable chest computed tomography (CT) scan, the patient developed progressive respiratory failure, requiring high-flow oxygen therapy. Molecular testing using the BIOFIRE® FILMARRAY® Pneumonia Panel Plus identified HMPV and influenza A virus as the causative pathogens. Bacterial cultures were negative, allowing for the discontinuation of empirical antibiotic therapy. The patient was successfully weaned off oxygen therapy and discharged after clinical improvement. Conclusions: This case highlights the potential severity of HMPV and influenza A co-infection in PLWH, emphasizing the importance of molecular diagnostics in distinguishing viral from bacterial infections. Rapid and accurate pathogen identification is essential for guiding appropriate antimicrobial stewardship and optimizing patient outcomes in community-acquired pneumonia.